2019
DOI: 10.1080/15384101.2019.1577650
|View full text |Cite
|
Sign up to set email alerts
|

Atypical GATA protein TRPS1 plays indispensable roles in mouse two-cell embryo

Abstract: Zygotic genome activation (ZGA) is one of the most critical events at the beginning of mammalian preimplantation embryo development (PED). The mechanisms underlying mouse ZGA remain unclear although it has been widely studied. In the present study, we identified that tricho-rhinophalangeal syndrome 1 (TRPS1), an atypical GATA family member, is an important factor for ZGA in mouse PED. We found that the Trps1 mRNA level peaked at the one-cell stage while TRPS1 protein did so at the two/four-cell stage. Knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…Nevertheless, the functions and biochemical properties of the MuERVL gene have yet to be fully identified. A recent report also demonstrated that reduced H3K27me3 resulted in the up-regulation of ZGA marker genes in mouse embryos [37]. These results suggested that the H3K27me3 demethylase UTX serves as a novel MuERVL regulator and is essential for preimplantation embryonic development.…”
Section: Discussionmentioning
confidence: 78%
“…Nevertheless, the functions and biochemical properties of the MuERVL gene have yet to be fully identified. A recent report also demonstrated that reduced H3K27me3 resulted in the up-regulation of ZGA marker genes in mouse embryos [37]. These results suggested that the H3K27me3 demethylase UTX serves as a novel MuERVL regulator and is essential for preimplantation embryonic development.…”
Section: Discussionmentioning
confidence: 78%
“…MuERV-L is one of the earliest transcribed genes in mouse 1-cell embryos (Kigami et al 2003 ) and promotes the expression of hundreds of neighboring genes (Schoorlemmer et al 2014 ). Other studies showed that the expression of MuERV-L was regulated by some maternal factors such as REX1 (Schoorlemmer et al 2014 ), TRPS1 (Liu et al 2019 ), and DPPA3 (Huang et al 2017 ), contributing to the epigenetic plasticity of mouse embryos. As H3K9me3 is known to be required for silencing ERVs (Elsässer et al 2015 ; Matsui et al 2010 ), Didier Trono’s group demonstrated that SETDB1 regulates the deposition of H3K9me3 and controls the activation of MuERV-L by interacting with KAP1 in ESCs (Rowe et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…H3K4me3 regulates the expression of important genes during early embryonic development, such as OCT-4, NANOG, SOX2, and CDX2 [11,12,37,38], and the expression of apoptosis-related genes (Bax, Bak, and Bcl) [39]. Therefore, H3K4me3 exhibits different modification patterns in different stages of embryonic development [11,12,37,38]. Before the activation of the zygotic genome, the H3K4me3 modification from the paternal chromosome will undergo extensive reprogramming.…”
Section: Discussionmentioning
confidence: 99%